2009
DOI: 10.1016/j.molbiopara.2009.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of expressed sequence tags from the four main developmental stages of Trypanosoma congolense

Abstract: Trypanosoma congolense is one of the most economically important pathogens of livestock in Africa. Culture-derived parasites of each of the three main insect stages of the T. congolense life cycle, i.e., the procyclic, epimastigote and metacyclic stages, and bloodstream stage parasites isolated from infected mice, were used to construct stage-specific cDNA libraries and expressed sequence tags (ESTs or cDNA clones) in each library were sequenced. Thirteen EST clusters encoding different variant surface glycopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
37
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 54 publications
4
37
0
Order By: Relevance
“…We also examined whether functional expressed VSGs of another African trypanosome species, Trypanosoma congolense , [2931] fall into similar N-terminal types. Using an E < 1e-03 threshold of similarity, 17 available T. congolense VSGs (as determined from cDNAs) occurred in the N4 N-terminal type (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also examined whether functional expressed VSGs of another African trypanosome species, Trypanosoma congolense , [2931] fall into similar N-terminal types. Using an E < 1e-03 threshold of similarity, 17 available T. congolense VSGs (as determined from cDNAs) occurred in the N4 N-terminal type (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Panels A – E contain 767 VSGs for which all annotation information is available, including N- and C-terminal sequences, chromosomal gene location and predicted functional annotations (functional, atypical, or pseudogene) [7, 8]. Panel F contains 17 additional expressed (cDNA) N-terminal VSG sequences from other T. brucei isolates [2528], and 17 expressed (cDNA) N-terminal VSG sequences from T. congolense [2931], for a total of 801 sequences. All panels were clustered according to similarity between the N-terminal VSG amino acid sequences determined by a BLAST hit of E < 1e-03.…”
Section: Figmentioning
confidence: 99%
“…Functional variant antigens in T. brucei consist of a-and b-type VSG (hereafter a-VSG and b-VSG), which share the cysteine-rich C-terminal domain (CTD) but are otherwise distantly related (9)(10)(11). Although VSG are known to occur in T. congolense and T. vivax (12)(13)(14)(15)(16), the repertoire of variant antigens in these species is uncharacterized. Consequently, the evolutionary diversification of the VSG gene family has not been examined, although it has been suggested that VSG are a source of novel genes.…”
mentioning
confidence: 99%
“…Hence, T. congolense b-VSG are more structurally heterogeneous than T. brucei b-VSG are. We know that both Fam13 and Fam16 contain functional variant antigens because each family encompasses both published T. congolense VSG (12)(13)(14) and VSG expressed sequence tags (15). Although there is no a-VSG variant antigen, there are homologs of the a-VSG-like TFR genes of T. brucei, i.e., ESAG6/7 (Fam15; n = 43), as well as the procyclin-associated genes (PAG) (Fam14, n = 22), which also have an a-VSG-like structure (20).…”
mentioning
confidence: 99%
“…T. congolense EMF parasites tightly adhere via their flagella to the lining of the labrum located in the mouthparts of tsetse fly by hemidesmosome-like structures [3]. Our previous studies reported that congolense epimastigote-specific protein (CESP) (accession number: AB300788) was exclusively translated in the EMF stage [4,5]. Eventually, EMF trypanosomes develop into the non-adherent animal-infective metacyclic form (MCF) and differentiate into the proliferating BSF in the new vertebrate host.…”
mentioning
confidence: 99%